PERANCANGAN SISTEM INFORMASI PENDATAAN BARANG MILIK NEGARA BERBASIS WEB PADA BADAN PUSAT STATISTIK BANYUWANGI - Qurratul Aini; Zaehol Fatah; Abdul Hadi (Jurnal Riset Sistem Informasi, 2025)
Advances in information technology are driving government agencies to improve data governance quickly, accurately, and in an integrated manner. The Banyuwangi Central Statistics Agency (BPS) requires a State Property (BMN) recording system capable of improving the quality of its governance. This system was designed to minimize errors in manual recording, expedite report preparation, and facilitate real-time data access. This research aims to create a web-based state property data collection information system using a prototype method, enabling active user and developer involvement from the design process through testing. This research obtained data through observation, interviews, studies, documentation, and references from various sources. The resulting system features incoming and outgoing goods data input, reporting, and automatic validation to avoid data duplication. This system is expected to strengthen BMN management at BPS Banyuwangi, facilitate digital transformation in administration, and serve as a reference for the application of information technology in government agencies.